Pengaruh Penerapan E-Samsat terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Dimoderasi oleh Sosialisasi Perpajakan - Apriliani, Kiki Rizki; Irawan, Arry (Jurnal Akuntansi Terapan dan Bisnis, 2025)
Motor vehicle taxpayer compliance is a key factor influencing provincial-level regional tax revenue. This revenue is crucial for funding local development. However, high levels of outstanding motor vehicle tax payments in many regions, including Subang, indicate low taxpayer compliance. This study examines the effect of implementing E, Samsat, on motor vehicle taxpayer compliance, moderated by tax socialization efforts at the Subang District SAMSAT office. A quantitative research design was employed, using random sampling to select respondents from the population of motor vehicle taxpayers registered at the Subang SAMSAT office. A sample of 100 respondents was determined using the Slovin formula, and data were collected via questionnaires. Partial Least Squares Structural Equation Modeling (PLS,‑SEM) analysis was conducted using SmartPLS version 4.1.1.2. The findings indicate that the implementation of E, Samsat, has a positive effect on motor vehicle taxpayer compliance. However, tax socialization does not moderate this effect. These results suggest that, while E, Samsat, implementation has improved taxpayer compliance in Subang, existing tax socialization efforts have not yet strengthened this effect.